REKAYASA KINCIR AIR PADA TAMBAK LDPE UDANG VANNAMEI (Litopenaeus vannamei) DI TAMBAK UNIKAL SLAMARAN - Nurman Prasetya Adi Nugraha; Muhamad Agus; Tri Yusufi Mardiana (Fakultas Perikanan Universitas Pekalongan, 2017)
Vannamei shrimp’s culture (Litopenaeus vannamei) is need waterwheel as an oxygen supply. Density high require the amount wheendmill sufficient for the needs cultivan oxygen fulfilled. Therefore this study aimed to get the design waterwheel assemblies in the cultivation of vannamei shrimp and comparethe use of whind mills water paddel wheel. This research method is experimental design to make the design engeneering water wheel assemblies on the cultivation of vannamei shrimp in ponds result obtained design water wheel assemblies btained by the design of the water wheel using the first propulsion desel engeine 8 PK can move the two assemblies to maximize aeration process in the ponds with (area) at the same ponds, water wheel assemblies can move the eight (8) leaves the mill simultaneously the while (paddel using one engine to drive the dynamo 2 leaves movement resulted water more evenly wheel assemblies circulation well.Keywords : vannamei shrimp, assembled mills, paddel whell.